2017
DOI: 10.2147/cmar.s142677
|View full text |Cite
|
Sign up to set email alerts
|

<em>SIRT1</em> gene polymorphisms and risk of lung cancer

Abstract: ObjectiveLung cancer, which is the leading cause of cancer death worldwide, is influenced by a wide variety of environmental and genetic risk factors. The silent information regulator 1 (SIRT1) gene is located on the long arm of chromosome 10 (10q21.3) and has been shown to play crucial roles in lung cancer development in previous studies. In this study, we determined whether variation in the SIRT1 gene is associated with lung cancer in Chinese population.MethodsThe case–control study comprised 246 controls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
7
1
1
Order By: Relevance
“…SIRT1 rs3758391 was reported to be more common in Egyptian breast cancer patients than controls, as was rs12778366 46 . Rs12778366 was also one of the SIRT1 variants analyzed in a Chinese study on lung cancer risk, but this study showed no significant associations 47 . Lung cancer differs etiologically from CRC, making a comparison with these results more difficult, but (postmenopausal) breast cancer shares several risk factors with CRC, including body fatness 41 .…”
Section: Discussioncontrasting
confidence: 60%
“…SIRT1 rs3758391 was reported to be more common in Egyptian breast cancer patients than controls, as was rs12778366 46 . Rs12778366 was also one of the SIRT1 variants analyzed in a Chinese study on lung cancer risk, but this study showed no significant associations 47 . Lung cancer differs etiologically from CRC, making a comparison with these results more difficult, but (postmenopausal) breast cancer shares several risk factors with CRC, including body fatness 41 .…”
Section: Discussioncontrasting
confidence: 60%
“…These factors are essential for not only initiation and progression, but also metastasis of cancers ( 116 , 117 ). Mutations and extensive polymorphisms of SIRT1 were found in Chinese and Japanese ( 118 121 ) and 41 cancer lines ( 122 ). Although the data on mutations and polymorphisms of SIRT1 are very limited, we speculate that difference in SIRT1 mutations and polymorphisms may be one of accounts for difference in predicting OS and TNM stage and lymphatic metastasis of cancer by SIRT1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Lv and colleagues suggested that rs3758391 had no significant association with susceptibility of different lung cancer subtype. [ 41 ] T allele of rs3758391 was positively correlated with nephritis in patients with systemic lupus erythematosus. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%